The original and subsequent audiences of the Manuel des péchés and its Middle English descendants - Sullivan, M; Sullivan, Matthew Thomas (1990)
﻿ Chapter I examines the text of the Manuel des Péchés. A new concept of the genuine structure and subsequent corruption of the poem is evolved with close reference to internal and external (MS.) evidence. Previous claims that the Manuel was designed for the edification of laypeople are shown, with detailed attention to the text, to be indefensible. The poem is a tract which promotes observance of a sacramental law and which was designed for repeated study and absorption by a general clerical readership. Chapter II begins with an unprecedented positive identification and biography of the author of the Manuel. William of Waddington was a secular canon and a prominent figure in the legal hierarchy of the Diocese of York. The MS. circulation is thereafter investigated. Copies of the work almost instantly reached clerical individuals and institutions throughout England. Waddington's intended and achieved audiences are nearly identical. Chapter III considers the text of Handlyng Synne. It is demonstrated that this poem was not, as some have claimed, intended for systematic use in a program of education of the laity. It does not promote the sacrament of confession and it removes much of the reformative material in the Manuel. It was designed for random and selective group and individual reception by unsophisticated laypeople and clerics from' the author's region. Through local stories, a familiar tone, and an uncomplicated and leisurely style Robert Mannyng, the author, transformed the Manuel into a local story-book/directory of sin. Chapter IV traces the MS. circulation of Handlyng Synne. The poem was received for the most part by the ordinary lay and religious people for whom it was intended. Chapter V studies the text and MSS. of the stanzaic redaction of Handlyng Synne by Peter Idley. It is demonstrated for the first time that the work commonly called Idley's Instructions to His Son,/em> seems in fact to be two independent and internally unrelated poems (the second being the redaction of Mannyng's work) which initially circulated separately and which were subsequently fused by a scribe. A biography uncovering Idley's connections with literary society is provided. He transformed Mannyng's poem into a guide to prosperity for the prosperous. Deft additions to and deletions from his source often cunningly reassure men of position that wealth is a product of virtue, and largely irrelevant borrowings from Lydgate's Fall of Princes are appropriately fashionable. The MSS. indicate that the poem achieved geographically wide circulation among the prosperous laity for whom it was intended. These three poems were in practice received by the audiences for whom they were intended. While the texts share a common core of content, they are extremely different from each other in purpose and audience. There is, however, a fringe audience of interconnected northern landed families who took an interest in all three texts. At the center of this network is a family closely connected with the village of Waddington, Lancashire, the birthplace of the author of the Manuel, and more distantly linked with Mannyng's birthplace and with apparent ancestors of associates of Idley. These and other matters are developed in the nine appendices which conclude the thesis.